GnRH peripherally modulates nociceptor functions, exacerbating mechanical pain - Zheng, Haiyan; Kim, Minseok; Kim, Chaeun; Kim, Yerin; Cho, Pyung Sun; Lim, Ji Yeon; Lee, Hojin; Yun, Hye-In; Choi, Jungmin; Hwang, Sun Wook (Frontiers in Molecular Neuroscience, 2024)
The function of peripheral nociceptors, the neurons that relay pain signals to the brain, are frequently tuned by local and systemic modulator substances. In this context, neurohormonal effects are emerging as an important modulatory mechanism, but many aspects remain to be elucidated. Here we report that gonadotropin-releasing hormone (GnRH), a brain-specific neurohormone, can aggravate pain by acting on nociceptors in mice. GnRH and GnRHR, the receptor for GnRH, are expressed in a nociceptor subpopulation. Administration of GnRH and its analogue, localized for selectively affecting the peripheral neurons, deteriorated mechanical pain, which was reproducible in neuropathic conditions. Nociceptor function was promoted by GnRH treatment in vitro, which appears to involve specific sensory transient receptor potential ion channels. These data suggest that peripheral GnRH can positively modulate nociceptor activities in its receptor-specific manner, contributing to pain exacerbation. Our study indicates that GnRH plays an important role in neurohormonal pain modulation via a peripheral mechanism.